Too much of a good thing? striking a balance between research environment inputs and research output quality in UK business schools - Theoharakis, Vasilis; Batsakis, Georgios (Wiley, 2026)
The UK's Research Excellence Framework (REF) is one of the world's most established performance‐based research funding systems, shaping universities’ strategic choices. While the REF emphasizes investing in research inputs to enhance output quality, the investments in research environment inputs can, at some point, become counterproductive and lead to diminishing returns. Drawing on the research production function approach and the resource‐based view (RBV), we examine how universities transform research environment inputs into research outputs and impact. We empirically investigate whether the production functions relating research environment inputs (external research income and doctoral programme size) to research outcomes (output and impact quality) follow an inverted U‐shaped curve. Using REF2021 data on 108 UK business schools, we confirm that initial gains plateau and eventually decline as resources are stretched. We further find that Russell Group (RG) business schools operate under distinct production functions, enabling them to sustain research output quality with higher levels of external research input than non‐RG peers. However, they do not exhibit superior production functions for research impact as defined by the REF, despite potential advantages in global reach, suggesting that different institutional types have developed equally effective but distinct approaches to generating societal value.
Keywords: Business & Management; 3505 Human resources and industrial relations; 3506 Marketing; 3507 Strategy, management and organisational behaviour